KAJIAN DESKRIPTIF ANALITIS TENTANG TEORI HUKUM PEMBANGUNAN PROF. DR. MOCHTAR KUSUMAATMADJA, S.H., LL.M. - Manggala Yudha, Fernando; Mahardika Efendi, Candra; Wahyuni, Syaefa; Sembiring, Roy Andika Stevanus; Dirga Saputra, Dekrit; Bangsa Diria, Arya Ahmad; Ruslina, Elli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to provide an analytical descriptive study of the Development Law Theory proposed by Prof. Dr. Mochtar Kusumaatmadja, S.H., LL.M. As a legal theory formulated by considering Indonesia's social and cultural conditions, this theory emphasizes the importance of law as a means of community renewal in the context of national development. Development Law Theory asserts that order and regularity in development efforts are absolutely necessary, and law can function as a directional tool that channels human activities in the direction desired by the development process. This research also analyzes the historical and conceptual dimensions of this theory, including the influence of Roscoe Pound's theory “Law as a Tool of Social Engineering” as well as the thoughts of Harold D. Lasswell and Myres S. McDougal. By examining the structure, substance, and culture of law within a development framework, this study provides insight into the relevance and application of the theory in the pluralistic Indonesian context. The results of this study are expected to contribute to the development of laws that are adaptive and responsive to social dynamics in Indonesia.Keywords: Theory of Law Reform - Mochtar Kusumaatmadja - Development